Combustion of Methanol Droplets in Air-Diluent Environments with Reduced and Normal Gravity. (16th May 2012) - Shaw, Benjamin; Wei, Jingbin
Abstract : Reduced and normal gravity combustion experiments were performed with fiber-supported methanol droplets with initial diameters in the 1 mm size range. Experiments were performed with air-diluent mixtures at about 0.101 MPa and 298 K, where carbon dioxide, helium, or xenon was separately used as the diluent gas. Results indicate that ambient gas transport properties play an important role in determining flammability and combustion behaviors including burning rates and radiant heat output histories of the droplets. Droplets would burn with significantly higher mole fractions of xenon than helium or carbon dioxide. In reduced gravity, droplets would burn steadily with a xenon mole fraction of 0.50 but would not burn steadily if helium or carbon dioxide mole fractions were 0.50. Comparison with previous experimental data shows that ignitability and combustion characteristics of droplets are influenced by the fuel type and also the gravitational level. Burning rates were about 40% to 70% higher in normal gravity than in reduced gravity. Methanol droplets also had burning rates that were typically larger than 1-propanol burning rates by about 20% in reduced gravity. In normal gravity, however, burning rate differences between the two fuels were significantly smaller.